Solution :
Given :
a = (1, 2, 3, 4) , b = ( 4, 3, 2, 1), c = (1, 1, 1, 1) ∈ ![R^4](https://tex.z-dn.net/?f=R%5E4)
a). (a.2c)b + ||-3c||a
Now,
(a.2c) = (1, 2, 3, 4). 2 (1, 1, 1, 1)
= (2 + 4 + 6 + 6)
= 20
-3c = -3 (1, 1, 1, 1)
= (-3, -3, -3, -3)
||-3c|| = ![$\sqrt{(-3)^2 + (-3)^2 + (-3)^2 + (-3)^2 }$](https://tex.z-dn.net/?f=%24%5Csqrt%7B%28-3%29%5E2%20%2B%20%28-3%29%5E2%20%2B%20%28-3%29%5E2%20%2B%20%28-3%29%5E2%20%7D%24)
![$=\sqrt{9+9+9+9}$](https://tex.z-dn.net/?f=%24%3D%5Csqrt%7B9%2B9%2B9%2B9%7D%24)
![$=\sqrt{36}$](https://tex.z-dn.net/?f=%24%3D%5Csqrt%7B36%7D%24)
= 6
Therefore,
(a.2c)b + ||-3c||a = (20)(4, 3, 2, 1) + 6(1, 2, 3, 4)
= (80, 60, 40, 20) + (6, 12, 18, 24)
= (86, 72, 58, 44)
b). two vectors
and
are parallel to each other if they are scalar multiple of each other.
i.e.,
for the same scalar r.
Given
is parallel to
, for the same scalar r, we have
![$\vec p = r (1,2,3,4)$](https://tex.z-dn.net/?f=%24%5Cvec%20p%20%3D%20r%20%281%2C2%2C3%2C4%29%24)
......(1)
Let
......(2)
Now given
and
are perpendicular vectors, that is dot product of
and
is zero.
![$q_1r + 2q_2r + 3q_3r + 4q_4r = 0$](https://tex.z-dn.net/?f=%24q_1r%20%2B%202q_2r%20%2B%203q_3r%20%2B%204q_4r%20%3D%200%24)
.......(3)
Also given the sum of
and
is equal to
. So
![\vec p + \vec q = \vec b](https://tex.z-dn.net/?f=%5Cvec%20p%20%2B%20%5Cvec%20q%20%3D%20%5Cvec%20b)
![$(r,2r,3r,4r) + (q_1+q_2+q_3+q_4)=(4, 3,2,1)$](https://tex.z-dn.net/?f=%24%28r%2C2r%2C3r%2C4r%29%20%2B%20%28q_1%2Bq_2%2Bq_3%2Bq_4%29%3D%284%2C%203%2C2%2C1%29%24)
∴
....(4)
Putting the values of
in (3),we get
![r=\frac{2}{3}](https://tex.z-dn.net/?f=r%3D%5Cfrac%7B2%7D%7B3%7D)
So putting this value of r in (4), we get
![$\vec p =\left( \frac{2}{3}, \frac{4}{3}, 2, \frac{8}{3} \right)$](https://tex.z-dn.net/?f=%24%5Cvec%20p%20%3D%5Cleft%28%20%5Cfrac%7B2%7D%7B3%7D%2C%20%5Cfrac%7B4%7D%7B3%7D%2C%202%2C%20%5Cfrac%7B8%7D%7B3%7D%20%5Cright%29%24)
![$\vec q =\left( \frac{10}{3}, \frac{5}{3}, 0, \frac{-5}{3} \right)$](https://tex.z-dn.net/?f=%24%5Cvec%20q%20%3D%5Cleft%28%20%5Cfrac%7B10%7D%7B3%7D%2C%20%5Cfrac%7B5%7D%7B3%7D%2C%200%2C%20%5Cfrac%7B-5%7D%7B3%7D%20%5Cright%29%24)
These two vectors are perpendicular and satisfies the given condition.
c). Given terminal point is
is (-1, 1, 2, -2)
We know that,
Position vector = terminal point - initial point
Initial point = terminal point - position point
= (-1, 1, 2, -2) - (1, 2, 3, 4)
= (-2, -1, -1, -6)
d). ![\vec b = (4,3,2,1)](https://tex.z-dn.net/?f=%5Cvec%20b%20%3D%20%284%2C3%2C2%2C1%29)
Let us say a vector
is perpendicular to ![\vec b.](https://tex.z-dn.net/?f=%5Cvec%20b.)
Then, ![\vec b.\vec d = 0](https://tex.z-dn.net/?f=%5Cvec%20b.%5Cvec%20d%20%3D%200)
![$4d_1+3d_2+2d_3+d_4=0$](https://tex.z-dn.net/?f=%244d_1%2B3d_2%2B2d_3%2Bd_4%3D0%24)
![$d_4=-4d_1-3d_2-2d_3$](https://tex.z-dn.net/?f=%24d_4%3D-4d_1-3d_2-2d_3%24)
There are infinitely many vectors which satisfies this condition.
Let us choose arbitrary ![$d_1=1, d_2=1, d_3=2$](https://tex.z-dn.net/?f=%24d_1%3D1%2C%20d_2%3D1%2C%20d_3%3D2%24)
Therefore, ![$d_4=-4(-1)-3(1)-2(2)$](https://tex.z-dn.net/?f=%24d_4%3D-4%28-1%29-3%281%29-2%282%29%24)
= -3
The vector is (-1, 1, 2, -3) perpendicular to given ![\vec b.](https://tex.z-dn.net/?f=%5Cvec%20b.)